Features of protein, lipid, carbohydrate and mineral metabolism in descendants of female rats with various motor activities - T. V. Gorbach; M. S. Baranova (Zaporozhye State Medical University, 2018)
Hypokinetic living conditions of pregnant women are a very common situation in today's society. Aim. In order to study the features of the metabolic processes in the teeth of 84 descendants of female rats who were under conditions of different motor activity during gestation, content of biogenic elements in dentin and blood serum, protein, lipid and carbohydrate metabolism indicators in blood serum were studied. Results. We found that maternal hypokinesia reduces the content of inorganic components in the teeth of descendants. And brief daily motor exercises of hypokinetic pregnant female rats contribute to the improvement of metabolism.